Higher Order Thinking Skill (HOTs): EFL Students’ Levels and Challenges in Writing Discussion Sections of Theses - Syafryadin Syafryadin; Shanina Bt. Sharatol Ahmad Shah; Annisa Astrid (Journal of Languages and Language Teaching, 2023)
HOTS is essential to be owned by English education students, especially in writing discussion because it made them being critical in writing their discussion. Thus, tThis study aims to determine the level of HOTS in writing the discussion section of the thesis, the difficulties faced by students in criticizing research results in the discussion section of the thesis and the challenges faced by the thesis supervisor lecturers in guiding students to write critical discussions. This study was motivated by complaints from students who experienced difficulties in writing the discussion section of the thesis, so it was necessary to do research on this matter. One alternative solution that can be done is the implementation of students' HOTS in writing, so that students can better critique the results of research data analysis in the discussion section. This study applies case studies which are part of qualitative research. The samples of this study were 5 student thesis discussions from the University of Bengkulu English Language Education study program. This study uses writing rubrics and interview guides as research instruments. The data obtained was analyzed qualitatively by applying several stages such as data reduction, data presentation and drawing conclusions. The result showed that students implemented HOTS in writing their discussion, but only in the level of analyzing and evaluation. Students could not reach the level of creating. Another result showed that students faced problems in writing their discussion, either technical problems, language problems, or content problems. It is the same as what happened to the lecturer supervisors. They got challenged in guiding students in writing their discussions. Their challenges were students’ language ability in writing, time management, ideas, and sources.